The effects of agrotechnological factors on winter wheat yield in humid cropyear - Vári, Enikő; Vad, Attila; Pepó, Péter (Acta Agraria Debreceniensis, 2010)
The effects of crop rotation, nutrien supply and crop protection technologies, as well as the appearance of the main ear- and leafdiseases(powdery mildew, helminthosporium leaf spot, leaf rust, fusarium) were studied on the crop yields of winter wheat variety MVPálma during the 2009/2010 crop year. The experiments were conducted in triculture (pea – wheat – corn) and biculture (wheat – corn), atfive nutrition levels, with the use of three crop protection technologies (extensive, conventional and intensive) at the Látókép Research Site ofthe University of Debrecen, Centre of Agricultural Sciences. Our results proved that the appearance of leaf- and ear-diseases weresignificant in the wheat cultures during the 2009/2010 crop year, because of the rainy, warmer than usual weather, the lodging, and the hugevegetative mass developed. The most severe infections by the four examined diseases after pea and corn pre-crops were observed atextensive crop protection levels, when fertilizers were used at the highest dose.Following corn pre-crop, in the case of all the three crop protection technologies the maximum rate of wheat yield results were achievedat N150+PK level. The highest yield was reached at intensive crop protection level (6079 kg ha-1). In triculture, in case of all the three cropprotection technologies the maximum yields were achieved at N50+PK level; in extensive technology 5041 kg·ha-1 yield, in conventionaltechnology 6190 kg ha-1 yield was realised, while in the intensive technological model the yield was 7228 kg ha-1.The relationship between yield and fertilizer amounts, the rate of pathogen contaminations, crop protection technologies and pre-cropswas defined with correlation analysis in case of different crop rotations during the 2009/2010 crop year. Based on the results of theexperiment, we found that in stands after corn pre-crop strong positive correlation was established between the crop protection level and thecrop yield (0.543), the nutrient levels and the emergence of the four examined pathogens, and between the nutrient levels and the yield(0.639). Extremly strong positive correlation was observed between crop protection and yield (0.843) in triculture. Strong positivecorrelation was detected between the nutrient levels and the presence of the four examined pathogens, as well as between nutrient andlodging (0.688). Strong negative correlation was between the crop protection level and the four examined diseases both in biculture andtriculture.